Romantic alternative monitoring increases ahead of infidelity and break-up. (February 2021) - Ritchie, Lane L.; Stanley, Scott M.; Rhoades, Galena K.; Markman, Howard J.
Monitoring alternative partners may be associated with engaging in behaviors that undermine relationship fidelity and/or stability. For example, paying attention to romantic alternatives has been shown to be associated with lower relationship quality. Studies have investigated the association between alternative monitoring and relationship outcomes, but with significant methodological limitations. This study aims to longitudinally explore whether and how alternative monitoring is associated with infidelity and break-up. Participants were 779 individuals drawn from a longitudinal sample of individuals in unmarried different-sex relationships. As hypothesized, alternative monitoring was higher for those who broke up and for those who reported infidelity, compared to those who remained together without infidelity. Additionally, consistent with predictions, increases in alternative monitoring preceded break-up, and particularly large increases in alternative monitoring preceded infidelity, compared to trajectories for those who remained together and did not report infidelity. Results highlight the importance of measuring change in alternative monitoring over time, rather than only considering mean differences at a single timepoint. Clinical implications and future directions are discussed.